2017
DOI: 10.1016/j.ymgme.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations for mitochondrial disease across the lifespan in the U.S.

Abstract: Importance Mitochondrial disease is being diagnosed with increasing frequency. Although children with mitochondrial disease often have severe, life-limiting illnesses, many survive into adulthood. There is, however, limited information about the impact of mitochondrial disease on healthcare utilization in the U.S. across the lifespan. Objectives To describe the characteristics of inpatient hospitalizations related to mitochondrial disease in the U.S., to identify patient-level clinical factors associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
2
9
1
Order By: Relevance
“…Accordingly, we do not agree with the figure 1:4300 for the prevalence of MIDs [1] . Nonspecific MIDs are regarded much more frequent occurring with a prevalence of 1:400 [4] .…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we do not agree with the figure 1:4300 for the prevalence of MIDs [1] . Nonspecific MIDs are regarded much more frequent occurring with a prevalence of 1:400 [4] .…”
contrasting
confidence: 99%
“…We read with interest the article by McCormack et al about frequency and costs of hospitalisations of mitochondrial disorder (MID) patients in California [1] . There are several reasons why the figures provided are underestimations.…”
mentioning
confidence: 99%
“…The severity of illness for MD is such that hospitalization and surgeries for some patients are unavoidable. A previous study using the Kids’ Inpatient Database and the National Inpatient Survey from the Healthcare Cost and Utilization Project (HCUP) showed that hospitalizations for mitochondrial disease is associated with substantial costs estimated at $113 million in 2012 [ 18 ]. In our analysis we found that total health care cost for pediatric MD was greater than that of adult MD ($4829 vs. $3100).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the multi-systemic nature of MD affecting any organ with any degree of severity and requiring chronic as well as acute care through high increase in emergency medicine resources. The HCUP study showed that in children, emergency room visits were associated with higher in-hospital mortality [ 18 ]. Although the lungs are typically not directly involved in the clinical manifestation of MD, neuromuscular and CNS involvement may affect ventilation, both the ventilator drive as well as motor control, and mistakenly get classified as a primary pulmonary problem.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8,9 ] A delay in clinical symptoms has suggested involvement of toxic events from environmental pollutants such as cigarette smoke, which may evoke or enhance MtD. [ 10,11 ] Children of white and non‐Hispanic ancestry with a higher median income have been reported to have a higher prevalence of MtD [ 12 ] ; however, the phenotypes and genetic abnormalities of MtD have been increasing since earlier investigations in 1988, [ 13 ] which has raised the question of environmental influences. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%